Philosophical aspects of the historical development of Islamic civilization and the interest in the teachings of Ibn Taymiyyah (1263-1328) - Maevskaya, Ludmila B.; Aga, Khaisam Muhammad (Linguistics and Culture Review, 2021)
The purpose of the paper is to analyse the philosophical aspects of the historical development of Islamic civilisation. Special attention is paid to the socio-cultural and socio-political crises that accompany the development of the Muslim world and the regularity of turning to the radical ideas of the Syrian religious figure Ibn Taymiyyah during the period of instability at the turn of the 13th-14th centuries. Theoretical basis: In the course of the study the author did not find any works, devoted to the influence of Ibn Taymiyyah on the establishment of the ideology of modern radical groups and the interest in the Islamic world to his ideas. Therefore, the scientific novelty of the study lies in the possibility to investigate the features of the historical development of the Islamic world and the appeal in times of crisis to the teachings of this medieval religious leader. In the course of the study the author came to the conclusion, the development of Islam was greatly influenced by the peculiarities of tribal relations in the Arab society in particular, and in the Islamic society as a whole.